Evaluation of point-of-care activated partial thromboplastin time testing by comparison to laboratory-based assay for control of intravenous heparin. - Douglas, A; Jefferis, J; Sharma, R; Parker, R; Handa, A; Chantler, J (2009)
INTRODUCTION: Patients on intravenous heparin require regular activated partial thromboplastin time monitoring. Laboratory-based activated partial thromboplastin time assays necessitate a delay between blood sampling and dose adjustment. Point-of-care testing could permit immediate dose adjustments, potentially enabling tighter control of anticoagulation. AIM: To assess equivalence of activated partial thromboplastin time measured by conventional laboratory assay and by a novel proprietary point-of-care testing system (Hemochron Response, ITC, Thoratec Corporation, Edison, NJ) among surgical ward patients on intravenous heparin. METHODS: A total of 39 blood samples from patients on intravenous heparin were tested with both laboratory and point-of-care assays. Assay equivalence was assessed by Bland-Altman analysis. Results. Point-of-care measurements exceeded laboratory activated partial thromboplastin time by a mean of 15 seconds (standard deviation 19). In 19 cases (49%), the point-of-care measurement would have resulted in different heparin dosing from the laboratory activated partial thromboplastin time. CONCLUSIONS: The Hemochron Response system is not sufficiently accurate for routine ward use compared with laboratory activated partial thromboplastin time assays.